2015
DOI: 10.1590/0100-69912015004002
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and brief intervention for trauma victims

Abstract: the motorcycle accident was the most common cause of injury. The detection of problematic alcohol use and implementation of BI are important strategies in the ED, however for alcohol abusers and dependents, BI was not the most reported reason for any changes in patterns of alcohol use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The ApoE knockout mouse is more suitable for presenting a deficiency in the gene encoding ApoE and for being predisposed to hypercholesterolemia inducing atherosclerosis. This and an already validated model are widely used in trials 3 , 16 , 18 , 20 , 21 , 22 , 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ApoE knockout mouse is more suitable for presenting a deficiency in the gene encoding ApoE and for being predisposed to hypercholesterolemia inducing atherosclerosis. This and an already validated model are widely used in trials 3 , 16 , 18 , 20 , 21 , 22 , 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was shown that the grape bark extract decreased blood glucose in experimental model of diabetes, which leads to the belief that the use of wine also has the same effect, since the phenolic compounds are present in the grape bark, basic raw material in wine production 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the retrospective studies, 15 reported that injured patients were routinely tested [35, 37, 39, 42, 68, 69, 72, 77–79, 84, 87, 89, 93, 97, 107] and 9 reported non‐routine approaches (e.g., at the discretion of clinicians or site‐specific policies) [56, 60, 61, 80, 85, 90, 91, 95]. Of the 15 consent‐based studies, 10 used consecutive sampling methods where consent was sought from all patients who met the study's eligibility criteria [31, 33, 36, 52, 53, 57, 62, 105, 111, 112], 3 used probability sampling (e.g., approached consecutive arrivals during set shifts that were representative of various times and days of the week) [103, 104, 113] and 2 obtained retrospective consent after using a waiver of consent to collect samples [108, 109]. Testing or recruitment approach was reported in 18 (49%) studies that examined drugs other than alcohol.…”
Section: Resultsmentioning
confidence: 99%
“…Another challenge is weaving, creating turbulence, impacting progress, and resulting in low capacity and creating bottlenecks in road systems [ 96 ]. The leading cause of death in road traffic accidents [ 164 ] is the increased injuries sustained in road crashes [ 8 , 12 , 26 , 42 , 66 , 74 , 75 , 118 , 152 , 154 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 ]. Previous studies indicated that approximately one-quarter of mortalities from traffic accidents involved motorcycle drivers [ 33 , 47 , 51 , 159 , 173 , 174 ].…”
Section: Discussionmentioning
confidence: 99%